Efficient Thermolysis Route to Monodisperse Cu(2)ZnSnS(4) Nanocrystals with Controlled Shape and Structure - Zhang, Xiaoyan (Sci Rep, 2014)
Monodisperse Cu(2)ZnSnS(4) (CZTS) nanocrystals with tunable shape, crystalline phase, and composition are synthesized by efficient thermolysis of a single source precursor of mixed metal-oleate complexes in hot organic solvents with dissolved sulfur sources. Suitable tuning of the synthetic conditions and the Cu/(Zn + Sn) ratio of the precursor has enabled precise control of the crystalline phase in the form of kesterite, or a newly observed wurtzite structure. Nanocrystals with morphology in the form of spherical, rice-like, or rod-like shapes are obtained over a wide range of compositions (0.5 ≤ Cu/(Zn + Sn) ≤ 1.2). Both the final products and intermediates for each shape exhibit consistent composition and structure, indicating homogenous nucleation and growth of single-phase nanocrystals. Thin films prepared from colloidal nanocrystal suspensions display interesting shape-dependent photoresponse behavior under white light illumination from a solar simulator.